Static magnetic field effects on proteases with fibrinolytic activity produced by Mucor subtilissimus. Issue 2 (14th November 2016) - Albuquerque, Wendell; Nascimento, Thiago; Brandão‐Costa, Romero; Fernandes, Thiago; Porto, Ana
Abstract : The influence of a static magnetic field (SMF) on crude enzyme extracts with proteolytic activity is described and discussed. Proteolytic enzymes, which hydrolyze peptide bonds, and fibrinolytic enzymes, which dissolve fibrin clots, have industrial relevance, and applicability dependent on improvements of productivity and activity. We investigated whether a moderate SMF affects proteolysis in different in vitro tests: general proteolysis of azocasein substrate, and static and dynamic fibrinolytic processes (to compare fibrin gel configuration under exposure). Crude enzyme extracts, obtained from solid state fermentation of Mucor subtilissimus UCP (Universidade Católica de Pernambuco, Recife, Brazil) 1262, were used to carry out assays under slightly heterogeneous fields: a varied vertical SMF (for tests in Eppendorf tubes, from 0.100 to 0.170 T) and a varied horizontal SMF (for tests in Petri dishes, from 0.01 to 0.122 T), generated by two permanent magnets (NdFeB alloy). Results showed significant differences ( P < 0.05) in static fibrinolysis assays after 24 h of exposure. The mean diameter of halos of fibrin degradation in the treated group increased by 21% compared to the control group; and the pixel number count of fibrin consumption (in a computational analysis of the area of each halo) enhanced by 30% with exposure. However, in dynamic fibrinolysis assays, no effects of SMF were observed. These results suggest a response of fibrin monomers to the SMF as a possible cause of the observed effects. Bioelectromagnetics. 38:109–120, 2017. © 2016 Wiley Periodicals, Inc.